Ru(III) CATALYSED OXIDATION OF EDTA BY N BROMOPHTHALIAMIDE IN AQUEOUS ALKALINE MEDIUM –A KINETIC AND MECHANISTIC STUDY (Indian Journal of Chemistry (IJC), 2024)
The studies involving the NBP oxidations are extensive in acid medium, while that in alkaline medium is very little. The mechanistic study of these reactions have been reported [1,2,3]. Bromamine- B is a mild oxidizing agent and is found to be better oxidizing agent than the chloro compounds. The disodium salt of ethylenediaminetetraacetic acid Na2H2Y or EDTA is known as oxidizing as well as chelating and used for the detection of metal ions in the acid and alkaline media. Kinetic study of oxidation of glycine and L-alanine by NBP using SDS was reported in the earlier work. Different workers have acknowledged unlike products with unusual oxidants for EDTA oxidation. In the recent year a homogeneous catalyst ruthenium(III) plays very important role in acidic and alkaline media. It forms various intermediate complexes, oxidation states and free radicals. The mechanism of catalysis depends on the nature of the substrate, oxidant and other experimental conditions followed by different paths like formation of a complex with reactants. Herein, we account the Ru(III) catalyzed oxidation of EDTA by NBP to get the hopeful mechanism and immediate species of oxidant, reductant and catalyst.